2021
DOI: 10.5539/jas.v13n2p95
|View full text |Cite
|
Sign up to set email alerts
|

Cowpea Response to Two Organic Fertilizers in the Nord Sudan Zone of Burkina Faso

Abstract: The Intensification of cowpea production is a priority because of its role in household income generation and its contribution to food security. To evaluate the effect of organic fertilizers on cowpea productivity, a dispersed block experiment design was set up in Saria in the semi-arid zone of Burkina Faso during the 2017 and 2018 cropping seasons. The combination of Biodeposit (Agro and Elixir) and Organova were used alone or in combination with mineral fertilizer. The results showed that during the two year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The result is supported with the findings of Yadav et al (2019) and Sakpal et al (2021). Ouedraogo et al (2021) found increased grain and biomass yields of cow pea in combination with organic and recommended mineral fertilizer dose.…”
Section: Agronomic Characteristics Of Cow Peamentioning
confidence: 92%
See 1 more Smart Citation
“…The result is supported with the findings of Yadav et al (2019) and Sakpal et al (2021). Ouedraogo et al (2021) found increased grain and biomass yields of cow pea in combination with organic and recommended mineral fertilizer dose.…”
Section: Agronomic Characteristics Of Cow Peamentioning
confidence: 92%
“…Replacing inorganic chemicals with organic one is effective in reducing environment pollution and producing safe food for human being (El-Sharawy et al, 2018). However, the increase in growth and yield of cowpea plant depends both on the boosting of soil fertility through the application of organic amendments and the use of fertilizers (Ouedraogo et al, 2021). There is little information available on the growth of cow pea plant in Bangladesh with the application of organic fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…Asfaw and Neka (2017), Kumar et al (2021), and Mondal et al (2018) demonstrated the soil and water conservation (SWC) structures significantly reduce soil erosion while improving crop yield. However, some studies have further investigated the benefits of optimizing fertility through microdosing on crop yields (Marenya et al, 2020;Ouedraogo et al, 2021;Timilsena et al, 2015;Traore et al, 2019). In addition, Kassie et al (2011), Manda et al (2016), and Zeeshan et al (2021) showed that fertilizer management significantly improves household income.…”
Section: Background and Purposementioning
confidence: 99%